Bulky bracelet jewellery: inspired by Malaysian batik / Muhammad Aiman Mohd Taufek - Mohd Taufek, Muhammad Aiman (2022)
A technique of hand-dyeing fabrics by using wax as a dye repellent to cover parts of a design. An ornamental band or ring, for the wrist or the arm; in modern times, an ornament.